2021
DOI: 10.1021/acscatal.1c04262
|View full text |Cite
|
Sign up to set email alerts
|

Thermokinetic and Spectroscopic Mapping of Carbon Monoxide Adsorption on Highly Dispersed Pt/γ-Al2O3

Abstract: The understanding and quantification of the CO adsorption modes and strength on ultradispersed platinum catalysts supported on γ-Al2O3 is of prominent importance for analytic and catalytic purposes. We report a multiscale experimental (AEIR, CO-TPD) and theoretical approach to provide vibrational properties, adsorption enthalpies, and desorption behaviors. First principles calculations on Pt13(CO) m /γ-Al2O3 and Pt(111) surface models (using various exchange-correlation functionals) provide a complementary vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 100 publications
1
19
0
Order By: Relevance
“…To examine whether WO x loading resulted in deposition on the surface of Pt nanoparticles, the adsorption of CO as a probe molecule was investigated using DRIFTS (Figure b). Such measurements reveal the electronic and structural characteristics of Pt sites by observing the vibrational frequency of the CO bond, , and adsorption of CO on WO x is not expected at room temperature . While STEM images demonstrated that WO x existed indiscriminately across the catalyst surface, previous work has demonstrated that the WO x structure evolves dynamically under reaction conditions, leading to the decoration of reduced metal nanoparticle surfaces. , To explore this, particularly following the reduction of the catalyst before catalytic activity measurements, catalysts were pretreated at 598 K in 10% H 2 /Ar to dehydrate the catalyst, fully reduce Pt, and facilitate WO x mobility prior to CO adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…To examine whether WO x loading resulted in deposition on the surface of Pt nanoparticles, the adsorption of CO as a probe molecule was investigated using DRIFTS (Figure b). Such measurements reveal the electronic and structural characteristics of Pt sites by observing the vibrational frequency of the CO bond, , and adsorption of CO on WO x is not expected at room temperature . While STEM images demonstrated that WO x existed indiscriminately across the catalyst surface, previous work has demonstrated that the WO x structure evolves dynamically under reaction conditions, leading to the decoration of reduced metal nanoparticle surfaces. , To explore this, particularly following the reduction of the catalyst before catalytic activity measurements, catalysts were pretreated at 598 K in 10% H 2 /Ar to dehydrate the catalyst, fully reduce Pt, and facilitate WO x mobility prior to CO adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Aluminas are highly valued materials for their versatility in various catalytic processes such as biomass conversion, 1,2 olefin metathesis, 3,4 natural gas conversion, 5 petrochemistry, 5,6 and exhaust gas cleaning, 7,8 as a result of their tunable surface physicochemical properties. 6 γ-Alumina (γ-Al 2 O 3 ) is one of the most widely used alumina polymorphs.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminas are highly valued materials for their versatility in various catalytic processes such as biomass conversion, , olefin metathesis, , natural gas conversion, petrochemistry, , and exhaust gas cleaning, , as a result of their tunable surface physicochemical properties . γ-Alumina (γ-Al 2 O 3 ) is one of the most widely used alumina polymorphs. , Since the early work of Knözinger and Ratnasamy, the nature and atomic-scale structure of surface hydroxyl (−OH) groups on γ-Al 2 O 3 surface have been thoroughly examined using various spectroscopic and computational approaches. ,, This extensive search for an ever more refined determination of the γ-Al 2 O 3 surface chemistry is motivated by the need to better control, on the one hand, the intrinsic reactivity driven by the Brønsted and Lewis surface sites for various reactions, , and on the other hand, the grafting, impregnation, and activation of metal precursors on γ-Al 2 O 3 acting as a catalytic support. ,, However, the surface structural features of γ-Al 2 O 3 are still questioned due to its complexity at multiple scales, from crystallite morphology to crystallinity or hydration level.…”
Section: Introductionmentioning
confidence: 99%
“…Alumina‐supported catalyst is widely used for industry catalytic processes due to their high structural stability and low cost [1–7] . However, there are also disadvantages of insufficient surface active sites and inappropriate electronic structure, which do not facilitate the catalytic process.…”
Section: Introductionmentioning
confidence: 99%